2019
DOI: 10.3390/ijms20225751
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Ameliorates DSS-Induced Ulcerative Colitis Mice by Enhancing Intestinal Barrier Function and Improving Microflora

Abstract: Ulcerative colitis (UC) has been identified as one of the inflammatory diseases. Intestinal mucosal barrier function and microflora play major roles in UC. Modified-chitosan products have been consumed as effective and safe drugs to treat UC. The present work aimed to investigate the effect of chitosan (CS) on intestinal microflora and intestinal barrier function in dextran sulfate sodium (DSS)-induced UC mice and to explore the underlying mechanisms. KM (Kunming) mice received water/CS (250, 150 mg/kg) for 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 31 publications
6
92
1
Order By: Relevance
“…It was also reported that Mel treatment increased the Lactobacillus spp. counts in large intestines of colitic mice which was consistent with present study (Wang et al 2019). It can be also expressed that Cd+Mel treatment may be reduced Enterobacteriaceae count and lead to increase Lactobacillus spp./Lactococcus spp.…”
Section: Resultssupporting
confidence: 92%
“…It was also reported that Mel treatment increased the Lactobacillus spp. counts in large intestines of colitic mice which was consistent with present study (Wang et al 2019). It can be also expressed that Cd+Mel treatment may be reduced Enterobacteriaceae count and lead to increase Lactobacillus spp./Lactococcus spp.…”
Section: Resultssupporting
confidence: 92%
“…consume H 2 generated from fermentation of sugars, relieving the inhibition of further fermentation reactions and displayed increased relative abundance in an herb-specific manner. This genus has been associated with improved barrier function and reduced inflammation in models of murine ulcerative colitis in response to chitosan supplementation ( Wang et al, 2019 ). Blautia producta reduced poly (I:C)-induced inflammatory cytokine expression in HT-29 cells ( Pathmanathan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…FCS may also have had indirect protective actions. DSS disrupts the intestine microbiota, leading to loss of protective and short-chain fatty acid (SCFA)-producing bacteria and a concomitant expansion in the populations of opportunistic pathobionts [ 40 , 41 , 42 ]. In previous studies, FCS partially ameliorated intestinal dysbiosis associated with experimental metabolic syndromes [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%